The Independent Party Panacea? - Shea, Daniel (Maine Policy Review, 2019)
In this commentary, Daniel M. Shea considers whether the addition of another party would redeem our faith in elections and cure the ills of governance.
Keywords: Maine; politics; political parties; third-party candidates